A New Approach for Finding out the Bioaccumulation Rate of Heavy Metals in Tissues of Liza parsia - B.C., Mohapatra; K., Rengarajan (Fishery Technology, 2025)
Through field and laboratory studies, a concept has been developed for finding out the differential rate of bioaccumulation of some heavy metals such as copper, zinc and lead in different tissues of mullet Liza parsia (Hamilton-Buchanan). This new approach for finding out the maximum bioaccumulation employed a series of experiments, statistical and graphical interpretations and has put forth a concept for future investigations with different bio-accumulative toxicants.